Application of the Questions Student Have to Improve Activities and Results of Learning Students - Masnur Masnur; Muh. Abrar Usman (Majesty Journal, 2019)
This study aimed to examine the effectiveness of the Questions Students Have learning model in improving students’ learning activities and science learning outcomes at SDN 166 Pinrang in the 2018/2019 academic year. The study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 30 fifth-grade students, comprising 16 boys and 14 girls. Data were collected through observation sheets and achievement tests. The findings showed that the implementation of the Questions Students Have model improved both student participation and academic achievement. In Cycle I, the average percentage of student activity reached 69%, and it increased to 85% in Cycle II. Similarly, students’ learning outcomes improved substantially. Classical mastery in Cycle I was 53.33%, with an average score of 63.41%, while in Cycle II it rose to 83.33%, with an average score of 85.48%. These results indicate that the model encouraged students to be more active in asking questions, responding to peers, and engaging in classroom discussion. The study concludes that the Questions Students Have learning model is effective in enhancing both learning activities and science learning outcomes of fifth-grade elementary students.